Synthesis, physical-chemical properties and research of acute toxicity of 1,2,4-triazole derivatives containing thiophene core - V. A. Salionov (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The aim of research. Modern drugs must have certain characteristics, such as low toxicity and high efficiency. Special attention should be given to esthers of 2-(1,2,4-triazoles-3-iltio)acetic acids. It has been found that compounds of this class are able to show analgesic, neuroleptic, diuretic, anti-inflammatory, mild antimicrobial and other biological activities and also can be intermediates for the synthesis of amides, hydrazides, ilidenhidrazides and bicyclic structures.